The Effect of Gender and Attentional Focus on Postural Control in the Elderly - Mandana Sangari; Seyed Mohammadkazem Vaez Mousavi; Parvaneh Shamsipour Dehkordi; Mahdi Namazizadeh (University of Social Welfare & Rehabilitation Sciences, 2018)
Objectives This study aimed to compare the effects of sex and different types of attentional focus of supra-postural tasks on postural control learning in older adults. Methods & Materials A total of 80 older adults (mean [SD] age: 72.5[4.9] year) participated in this study. The participants, selected according to inclusion criteria, were randomly divided into eight groups of internal and external attentional focus based on supra-postural cognitive and motor task guidelines. The postural status was evaluated by measuring the centre of gravity alignment through a master balancing system (modified clinical test of sensory interaction and balance). Results The results showed that the men's older adults with external focus in motor supra-postural task, had a better posture performance than the other groups (P<0.05). Women older adults with internal focus in cognitive supra-postural tasks had the weakest status in postural control function. Men and women also had a better postural control function than the other test groups in external attentional focus. Conclusion Postural control loss is greater in older women than men according to the impact of focusing attention on postural control. It is possible to improve the balance by planning external focus in supra-postural task programs.